A ciência nos meios de comunicação de massa: divulgação de conhecimento ou reforço do imaginário social? - Pechula, Márcia Reami [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2007)
The text describes the context of the theoretical-methodological crisis of modern science established in the XX century as opposed to the present social imaginary in the reception of science disclosed in mass communication. The analysis demonstrates that there is a paradox between the production of scientific knowledge forged in scientific institutions and the general vision of those that receive the scientific information through means of mass communication. The work has four consecutive themes: firstly, it describes the process of the theoretical-methodological crisis of science in the XX century in the academic realm; later on, it analyzes the formation of the constituent social elements of the imaginary, from a sociological perspective; in the third section , it analyzes the conditions of science as information within mass communication. And, lastly, it describes the means of mass communication with its scientific popularization, exemplified by the reading of the magazine Superinteressante.

O texto descreve a crise teórico-metodológica da ciência moderna instaurada no século XX, contraposta ao imaginário social presente na recepção da ciência divulgada pelos meios de comunicação de massa. A descrição demonstra que há um paradoxo entre a produção do conhecimento científico, forjado nos centros e instituições científicas, e a visão geral daqueles que recebem as informações científicas via meios de comunicação de massa. Para tanto, o trabalho estrutura-se em quatro etapas: 1º) descreve o processo da crise teórico-metodológica da ciência no século XX, no âmbito acadêmico; 2º) analisa a formação dos elementos constitutivos do imaginário social, sob a perspectiva sociológica; 3º) analisa as condições da ciência como informação nos meios de comunicação de massa; 4º) demonstra a veiculação das informações científicas dos meios de comunicação de massa, exemplificada pela leitura da revista Superinteressante.
The Science in mass communication: popularization of knowledge or social reinforcement of the imaginary?
Keywords: Science; Social imaginary; Means of mass communication; Ciência; Imaginário social; Meios de comunicação de massa